The Efficiency of Anaerobic Wastewater Stabilization Pond in Removing Phenol from Kermanshah Oil Refinery Wastewater - Ali Almasi; Meghdad Pirsaheb; Abdollah Dargahi (سلامت و محیط, 2012)
Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 Background and Objectives: Phenol is one of the aromatic compounds, which due to its high toxicity and its presence in the industrial effluents, should be removed and prevented it, to the receiving water resources. The natural biological plant has been accepted as one of the most feasible, eco-friendly and cost-effective options for the treatment of pollutants such as Phenol. The aim of this study is efficiency evaluation of the anaerobic stabilization pond performance in removing phenol and other organic compounds from Kermanshah oil refinery wastewater. Materials and Methods: The method of study was experimental and analytical, a laboratory scale anaerobic stabilization pond, with dimensions of 1 × 1 × 0/2 m, using fiberglass sheet with a thickness of 6 mm was designed and built up. In this study The hydraulic retention time and hydraulic loading rate were expected 2 days and 95 liters per day respectively. Organic loading rate for anaerobic pond was 100 g/m3. After starting, seeding and biological stability, samples were taken. Initial phenol concentration was added about of 100 mg/l to pilot input, then the parameters such as NH3, PO4 and Phenol were measured by Varian spectrophotometer model UV-120-02 in the wavelength 425, 690, 500 nm respectively. TCOD, SCOD, TBOD, SBOD, pH and ORP were measured according to the standard methods of water and wastewater. Results: The results showed that the removal efficiency of NH3, PO4, phenol, TCOD, SCOD, TBOD, SBOD in the anaerobic pond were obtained 91.51%, 64.34%, 89.82% 74.99 % 73.34% 71.75%, 68.9% respectively. Conclusion: The results showed that the ability for phenol and other organic compounds removal in anaerobic pond using petroleum refinery wastewater is higher than the other systems which are expensive and complex. st1":*{behavior:url(#ieooui) } /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Arial; mso-bidi-theme-font:minor-bidi;}